Does exposure to cigarette health warnings elicit psychological reactance in smokers? - Erceg-Hurn, David; Steed, Lyndall (Wiley-Blackwell Publishing Inc., 2011)
Researchers disagree as to whether cigarette warnings elicit psychological reactance in smokers. We used an experimental design to investigate whether (a) cigarette warnings elicit state reactance; and (b) the degree of reactance elicited by graphic cigarette warnings exceeds that elicited by text-only cigarette warnings. Smokers were exposed to graphic or text-only warnings and then completed reactance measures. Text-only warnings elicited little reactance, whereas over 80% of smokers who were exposed to graphic warnings experienced some reactance. Smokers who were exposed to graphic warnings were more likely to experience elevated and extreme levels of reactance. Our findings are consistent with recent studies indicating that graphic anti-smoking warnings can elicit maladaptive psychological responses.